Study on Bond Strength of Bonded Gray Cast Iron - Abdullah, Awfa Abdul-Rassol; Rawhdan, Rasha Rahman (Al-Nahrain Journal of Science, 2018)
In the present study, two gray cast iron specimens were diffusion bonded at the temperatures of 700, 750, 800, 850, and 900 °C, the furnace used atmosphericexperiment under a pressing load of 1 and 2 ton for 15, 30 and 60min. After diffusion bonding, shear test measurements of interface region were made. As a result, from the microstructural observations, a good bonding along the interface of the bonded couples were detected since the interface is free from voids and microcracks. To evaluate the bond strength, the shear test investigation was used. The actual bonded area was calculated by using a computer package called (Auto Cad 2006). The results shows that the bond strength increases with increasing the temperature and holding time. Fracturography of the interface was carried out by using optical microscope before and after the experiments. The microstructure results shows the formation of carbide. Its precipitation increases with increasing the bonding temperature and time.